Preparation and rheological investigation of tough PAAm hydrogel by adding branched polyethyleneimine. Issue 14 (22nd October 2019) - Guan, Yinyan; Wang, Li; Cui, Li; Shen, Xinjun; Gao, Weichun; Meng, Jing; Li, Dan; Shen, Chenguang; Zhang, Yichen; Hu, Guodong; Liang, Jiyan
ABSTRACT: In this article, tough hydrogels are prepared by introducing the polyethyleneimine (PEI) with branched structure and a large number of NH2 and NH groups into permanently crosslinked polyacrylamide (PAAm) hydrogels matrix. To investigate the effects of B‐PEI and chemical crosslinking agent (Bis) on the strength and toughness of hydrogels, a series of B‐PEI/PAAm hydrogels with different mass percentage of Bis and B‐PEI were manufactured and the rheological and swelling properties were compared. For all hydrogels, the storage modulus ( G ′) was much higher than the loss modulus ( G ″) in the linear viscoelastic region through the whole frequency range. The solid‐like behavior and elastic nature ( G ′ > G ″) are attributed to the permanent covalence crosslinking. Therefore, G ′ increased when more Bis was added. For the nonlinear oscillatory shear measurement, hydrogels with B‐PEI broke at larger γ than the pure PAAm hydrogels, indicating that the toughness of B‐PEI/PAAm hydrogels has been improved by introducing B‐PEI. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48541. Abstract :